Statistics for management and economics - Keller, Gerald (Singapore : Brooks/Cole Publishing Company, 2008)
Businesses are increasingly using statistical techniques to convert data into information. For students preparation for the business world, it is not enough merely to focus on mastering a diverse set of statistical techniques and calculations.
1. What is statistics -- 2. Graphical and tabular descriptive techniques -- 3. Art and science of graphical presentations -- 4. Numerical descriptive techniques -- 5. Data Collection and Sampling -- 6. Probability -- 7. Random variables and discrete probability distributions -- 8. Continuous probability distributions -- 9. Sampling Distributions -- 10. Introduction to estimation -- 11. Introduction to hypothesis testing -- 12. Inference about comparing two population -- 13. Inference about comparing two populations -- 14. Statistical inference: Review of Chapters 12 and 13 -- 15. Analysis of variance -- 16. Chi-Squared tests -- 17. Simple Linear Regression and correlation -- 18. Multiple regression -- 19. Model Building -- 20. Time series analysis and forecasting -- 21. Nonparametic statistics -- 22. Statistical process control -- 23. Decision analysis -- 24. Statistical Inference: Conclusion.
Includes index.
Keywords: STATISTICS